PO042 Early-esli study: from early add-on to monotherapy with eslicarbazepine acetate. (1st December 2017) - Villanueva, V; Gómez, A; Garcés, M; Bermejo, P; Montoya, J; Toledo, M; López-González, FJ; Rodriguez, X; Campos, D; Martínez, P; Giner, P; Zurita, J; et al.
Abstract : Purpose: Real-life experience with eslicarbazepine acetate (ESL) after first monotherapy failure in a large series of patients with partial epilepsy Method: Multicenter, retrospective, 1 year, observational study. Inclusion criteria: 1) patients older than 18 years; 2) partial-onset seizures; 3) Failure of first monotherapy for any reason (efficacy, tolerability, compliance). Time-points for revision were at 3, 6 and 12 months. Main objectives were to assess efficacy and tolerability. Results: A total of 253 patients were collected. The one-year retention rate was 92.9%. The mean dose after 12 months was 903.6±267 mg (range 400–1600). At 12 months, the percentage of seizure-free patients was 62.3%, 82.5% were responders and 5.6% did worse. Along the follow-up 31.6% of the patients reported adverse events and 3.6% discontinued for that reason. The main side effects were somnolence (8.7%) and dizziness (5.1%). A total of 127 patients (50.2%) were converted to monotherapy for at least 6 months. In this group, 77.2% were seizure-free and 29.1% of the patients reported AE after 1 year. Conclusion: ESL outcome along 1 year follow-up after first monotherapy failure showed an optimal efficacy and tolerability profile. Half of patients were converted to monotherapy and followed for at least 6 months.